Barriers among adolescent female to involve in physical activity / Muhammad Ameer Zhafri Abu Hasan - Abu Hasan, Muhammad Ameer Zhafri (Faculty of Sport Sciences and Recreation, 2020)
The purpose of this study is to identify barriers among adolescent female to involve in physical activity. Three hundred two female students (64.24% normal, 19.21% underweight, 13.25% overweight and 3.31% obese) from Universiti Teknologi Mara Campus Jengka Pahang were selected this study. The current study use Perceived Barriers to Physical Activity Questionnaire to measure barriers among adolescent female to involve in physical activity. The research design that used this study was cross sectional study. The data was analysed using descriptive analysis and Independent T Test. From the result internal barriers show the significant difference which were factor lack of energy (p=OOO) and external barriers value (p=033). It shows that internal barriers give the most impact towards physical activity among adolescents female.